ByzRev 06.2024.058: Maria Tomadaki, Iohannis Geometrae Carmina Iambica: (Corpus Christianorum Series Graeca 100). Turnhout: Brepols 2023. - Churik, Nikolas (The Byzantine Review, 2024)
Maria Tomadaki, Iohannis Geometrae Carmina Iambica (Corpus Christianorum Series Graeca 100). Turnhout: Brepols 2023. lviii, 211 pp. – ISBN 978-2-503-60447-3